Clinical features and metabolic complications for non-alcoholic fatty liver disease (NAFLD) in youth with obesity - Barbieri, Emiliano; Santoro, Nicola; Umano, Giuseppina Rosaria (Frontiers in Endocrinology, 2023)
Pediatric obesity has become in the last forty years the most common metabolic disease in children and adolescents affecting about 25% of the pediatric population in the western world. As obesity worsens, a whole-body insulin resistance (IR) occurs. This phenomenon is more pronounced during adolescence, when youth experience a high degree of insulin resistance due the production of growth hormone. As IR progresses, the blunted control of insulin on adipose tissue lipolysis causes an increased flux of fatty acids with FFA deposition in ectopic tissues and organs such as the liver, leading to the development of NAFLD. In this brief review, we will discuss the clinical implications of IR and NAFLD in the context of pediatric obesity. We will review 1- the pathogenesis and the link between these two entities, 2- the major pathophysiologic underpinnings, including the role of genetics and metagenomics, 3-how these two entities lead to development of type 2 diabetes.